Immobilization of Vanadium-Doped FeNi3 Alloy Nanoparticles in Carbon Spheres as a High-Efficiency Oxygen Evolution Electrocatalyst. Issue 13 (7th October 2020) - Wang, Fangmu; Li, Xiaoxiao; Qi, Xiaopeng; Liu, Chao; Liang, Tongxiang
Abstract : The development of high-performance non-noble metal catalysts to replace noble metal catalysts is a hot research topic at present. However, the low intrinsic activity of nonnoble metal catalysts often limits their development, and using heteroatoms to modify catalyst electronic structures is an efficient way to improve electrocatalyst performance. Herein, we successfully embed highly dispersed V-doped FeNi3 alloy nanoparticles into carbon spheres through a simple soaking adsorption method. The unique structure with nanoparticles coated by carbon can not only expose more active sites but can also increase the stability of the nanoparticles. As a result, the catalyst requires an overpotential of 293 mV for the OER to reach 10 mA cm −2 in 1 M KOH electrolyte. Density functional theory (DFT) calculations indicate that the substitution of the V atom for the Ni site in the FeNi3 alloy can effectively increase the d-band center compared with that of FeNi3 and thus strengthen the catalyst adsorption of reaction intermediates. This research can help us establish a new way to study alloy catalysts.